Primary Commodities : Market Developments and Outlook. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This study prepared by the Commodities Division of the Research Department reviews and analyzes the developments in commodity markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet